Epiperipatus hilkae, n. Sp. from Costa Rica (Onychophora: Peripatidae) - Morera-Brenes, Bernal (Universidad de Costa Rica, 1990)
Epiperipatus hilkae, a new species discovered in tropical dry and moist forests (NW Costa Rica) has the following characteristics: in the fourth and fifth oncopods, the nephridial tubercle is free from the third sole, and only partially surrounded by the fourth arco Each segment has 12 skin folds (seven folds reach the ventral side), which are divided only by the midline. The primary papillae are conical with rounded bases and two to three scale ranks in the apical section. The external jaw blade has two accessory teeth, the internal with one accessory tooth and 12 den tic les. The diastema is monolobular. The dorsal part is dark brown with a pattern of hexagons conspicuous for their light reddish- brown papillae. The new species is closely related to E.isthmicola and E. nicaraguensis, also from Central America. Jt remains active during the dry season in isolated moist patches